Modified Lancsos simulation of the localized superconductivity for a chain with interaction and disorder - Wiecko, C.; Chiappe, Guillermo (Comisión Nacional de Energía Atómica; Argentina, 1989)
Fil: Chiappe, Guillermo. Comisión Nacional de Energía Atómica; Argentina